1999
DOI: 10.1161/01.hyp.33.5.1141
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction and Baroreflex Sensitivity in Hypertension

Abstract: Abstract-The determinants of diastolic dysfunction in patients with systemic hypertension are not completely known. To evaluate the possible role of age, arterial blood pressure, and baroreflex heart rate response impairment in causing diastolic dysfunction, we studied 61 patients (42 male; meanϮSD age, 43.9Ϯ12 years) with newly recognized and therefore previously untreated systemic hypertension. Diastolic dysfunction was evaluated by means of Doppler echocardiography (and diagnosed as such when the early to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…Our data confirm a previous study by Pitzalis et al [33], performed in a small population of hypertensive patients, which showed an association between the mitral inflow E/A ratio and BRS. A major limitation of the evaluation of diastolic function using mitral inflow is the difficulty in identifying a pseudonormal pattern, resulting in the misdiagnosis of moderate diastolic dysfunction for a normal status.…”
Section: Discussionsupporting
confidence: 93%
“…Our data confirm a previous study by Pitzalis et al [33], performed in a small population of hypertensive patients, which showed an association between the mitral inflow E/A ratio and BRS. A major limitation of the evaluation of diastolic function using mitral inflow is the difficulty in identifying a pseudonormal pattern, resulting in the misdiagnosis of moderate diastolic dysfunction for a normal status.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are also in line with previous findings that hypertensive offspring are characterized by altered indexes of diastolic function [19,20], which we found to be independently related to plasma EO levels; that is, higher EO levels correlated with lower E/A ratios and a greater IVRT. These data are particularly interesting because it is generally accepted that diastolic abnormalities precede ventricular hypertrophy and, in two separate studies, we have recently identified a specific association between EO and left ventricular mass [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…24 -26 Furthermore, this is accompanied by a reduction in sensitivity of the parasympathetic component of the arterial baroreflex. 27 The data presented here give direct evidence that vagally induced bradycardia and radiolabeled acetylcholine release are significantly impaired in the hypertensive rat at the level of the postganglionic cholinergic synapse. This demonstrates that a signif- †PϽ0.05, paired t test) but not in the SHR (nϭ6).…”
Section: Defective Peripheral Cardiac Vagal Function In the Hypertensmentioning
confidence: 54%